PENERAPAN METODE PEMBELAJARAN INDEX CARD MATCH UNTUK MENINGKATKAN MINAT DAN PRESTASI BELAJAR MATEMATIKA SISWA KELAS III SD N WIROKERTEN - Defi Yuniantika; Esti Harini (Universitas Sarjanawiyata Tamansiswa, 2018)
Abstract: The purpose of the research is to describe the learning process by using the method of learning Index Card Match to increase interest and achievement of learning Mathematics at third grade students of SD N Wirokerten in the academic year 2016/2017. Subject of this research is third grade students of SD N Wirokerten, consist of 38 students. The data collecting technique are observation and test. The result of this research showed that interest and achievement of learning Mathematics using method of learning Index Card Match has improved. This is proven based of the results of data analysis on pre cycle student’s interest is 40,52%. In the cycle I increased to 57,37%. In the cycle II increased to 81,57%. In the pre cycle average score of the students results is 59,29 or as many 34,21% of students who reach KKM. In the cycle I has increased with an average score of the students results is 64,59 or as many 47,37% of students who reach KKM. In the cycle II has increased with an average score of the students results is 81,14 or as many 73,68% of students who reach KKM. The conclusion of the research is applying the method of learning Index Card Match can improve interest and achievement of learning Mathematics at third grade students of SD N Wirokerten in the academic year 2016/2017.